EDUCATION SYSTEM OF UZBEKISTAN.REFORMS AND INNOVATIONS IN EDUCATION.TYPES OF EDUCATIONAL INSTITUTION - Teshaboyeva Nafisa Zubaydulla qizi; Shodmonqulova Laziza Ilhom qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abctract.    This  article  provides  a  comprehensive  analysis  of  the  education system  of  the  Republic  of  Uzbekistan,  examining  its  current  structure,  ongoing reforms,  and  the  innovative  approaches  being  implemented  across  different educational stages. It offers an overview of the main types of educational institutions, including  preschool,  general  secondary,  vocational,  and  higher  education establishments. The study also highlights government initiatives, modern pedagogical methods,  digital  transformation processes,  and  mechanisms  of  quality  assurance  in education.  The  main  purpose  of  the  article  is  to  present  a  scientific  and  analytical assessment of the recent educational reforms in Uzbekistan, their effectiveness, and future development prospects.